2017
DOI: 10.1155/2017/5262560
|View full text |Cite
|
Sign up to set email alerts
|

Nonalcoholic Fatty Liver Disease and Associated Metabolic Risks of Hypertension in Type 2 Diabetes: A Cross-Sectional Community-Based Study

Abstract: The mechanisms facilitating hypertension in diabetes still remain to be elucidated. Nonalcoholic fatty liver disease (NAFLD), which is a higher risk factor for insulin resistance, shares many predisposing factors with diabetes. However, little work has been performed on the pathogenesis of hypertension in type 2 diabetes (T2DM) with NAFLD. The aim of this study is to investigate the prevalence of hypertension in different glycemic statuses and to analyze relationships between NAFLD, metabolic risks, and hypert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…[ 16 ] Additionally, Ding et al found that T2DM patients with NAFLD had significantly higher levels of systolic blood pressure and diastolic blood pressure than T2DM patients without NAFLD. [ 39 ] Based on these findings, it is deduced that NAFLD may be a hepatic manifestation of metabolic syndrome. [ 3 , 4 ] Consistently, this study found that the prevalence of NAFLD in T2DM patients differed significantly with differences in sample characteristics, including obesity, hypertension, and dyslipidemia.…”
Section: Discussionmentioning
confidence: 99%
“…[ 16 ] Additionally, Ding et al found that T2DM patients with NAFLD had significantly higher levels of systolic blood pressure and diastolic blood pressure than T2DM patients without NAFLD. [ 39 ] Based on these findings, it is deduced that NAFLD may be a hepatic manifestation of metabolic syndrome. [ 3 , 4 ] Consistently, this study found that the prevalence of NAFLD in T2DM patients differed significantly with differences in sample characteristics, including obesity, hypertension, and dyslipidemia.…”
Section: Discussionmentioning
confidence: 99%
“…Studies suggest that diagnosing NAFLD may identify those individuals at greater risk for metabolic dysfunction in T2DM (143,228). Epidemiological studies suggest that NAFLD and T2DM coexist (56,66). In a Chinese cohort, NAFLD was implicated in advancing T2DM (123).…”
Section: Nafld Is a Major Risk Factor For Uncontrolled Metabolic Diseasementioning
confidence: 99%
“…It is unknown whether the liver is a source of the circulating cytokines or whether they contribute to alterations in hypertension-induced CVRD and damage. Future studies are required to fully examine the contributions of hypertension and inflammation on the development of NAFLD and ensuing metabolic dysfunction and CVRD (56,127).…”
Section: Nafld As a Novel Risk Factor For Cvrdmentioning
confidence: 99%
“…NAFLD may also promote premature aging through promoting other metabolic risk factors such as telomerase length loss and hypertension [66]. In a well-controlled cross-sectional study, NAFLD was found to be associated with high prevalence of hypertension independent of other metabolic risk factors [106]. More in depth characterization of mechanisms of NAFLD should help to elucidate the most accurate diagnosis and therapeutics for individual elderly patients [107].…”
Section: Autophagy In Cardiovascular Aging - Action Of Metabolic Stressmentioning
confidence: 99%